Effects of phototherapy combined with Lactobacillus salivarius AP-32 or Bifidobacterium animalis subsp. lactis CP-9 on improving neonatal jaundice and gut microbiome health: a randomized double-blind clinical study - Ming-Luen Tsai; Shang-Po Shen; Yin-Ting Chen; Hsiao-Yu Chiu; Hsiang-Yu Lin; Hao-Wen Cheng; Yi-Wei Kuo; Jia-Hung Lin; Hui-Shan Wang; Yen-Yu Huang; Ching-Min Li; Yu-Hshun Chin; et al. (Nutrition Journal)
Abstract Neonatal jaundice is a common condition observed in newborns shortly after birth, making it one of the most frequent health concerns during the first two weeks of life. This study, conducted between May 2019 and July 2023, enrolled 300 full-term infants with bilirubin levels exceeding 15 mg/dL on the fourth day after birth. The infants were recruited and randomly assigned in equal numbers to one of three groups for further investigation. In addition to the control group, the other two groups of infants received probiotic supplementation administered twice daily, with each capsule delivering 5 × 10⁹ CFU of either Lactobacillus salivarius AP-32 or Bifidobacterium animalis subsp. lactis CP-9. Both probiotic groups significantly reduced the overall duration of phototherapy and accelerated the rate of bilirubin reduction compared to the control group. The AP-32 group experienced a significant reduction in hospitalization duration, staying seven hours less than the placebo group (P = 0.024). Analysis of gut microbiota revealed that the probiotic groups significantly enhanced microbial diversity in the intestines of neonates. The AP-32 group showed a significant increase in the abundance of L. salivarius, while the CP-9 group demonstrated a notable enhancement in the abundance of B. animalis. These findings suggest that integrating phototherapy with probiotic supplementation may enhance jaundice clearance increasing the abundance of beneficial gut bacteria, thereby facilitating the recovery of neonates.